REPRESENTASI PERUNDUNGAN (BULLIYING) PADA NOVEL DAN HUJAN PUN BERHENTI KARYA FARIDA SUSANTY: PENDEKATAN SOSIOLOGI SASTRA - Aidi Fitri; Lamria Naibaho; Seriana -; Friska Ria Sitorus (BIP: Jurnal Bahasa Indonesia Prima, 2023)
This research is motivated by the problem of rampant bullying that is currently happening in the community without exception, with the rampant bullying that often occurs among students, seen explicitly by researchers. Therefore, researchers are interested in exploring bullying. Based on the description above, it is necessary to conduct research. The writer is interested in analyzing the representation of bullying in the novel,